Incidence of Income Tax in the Mandate without Representation to Buy Goods - Hidalgo Vargas Machuca, Raúl Antonio (2014)
This article aims to determine the nature of the mandate without representation in the purchase of goods and their tax effects, so the author starts analyzing the corresponding figure of sending with and without representation, in order to understand its inner workings and confront within the tax Income. In that sense, the author believes that the president transfer of ownership is not onerous, each having different implications course within the income tax.